Improved complexation of paraquats with crown ether‐based pyridyl cryptands. Issue 6 (11th December 2017) - Price, Terry L.; Slebodnick, Carla; Gibson, Harry W.
Abstract: The commonly used paraquat guest N, N ′‐dimethyl‐4, 4′‐bipyridinium bis(hexafluorophosphate) (7 ) was targeted for structural alterations to improve the binding constants with crown ethers and cryptands. The association constant was improved by one order of magnitude (to K a = 1.00 × 10 6 mol L −1 ) with the dibenzo‐30‐crown‐10 pyridyl cryptand host5 by changing the N‐methyl groups to benzyl and the counterions from PF6 to TFSI, that is, 11 . Moreover, through addition of a p ‐bromobenzyloxy moiety on the 4‐position of the pyridyl ring of cryptand18, an association constant of K a = 5.35 × 10 6 mol L −1 was achieved with paraquat11 .